Pengaruh Penerapan Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Siswa Kelas XI MIA SMAN 2 Padang Tahun Pelajaran 2019/2020 - ELVI ALPIATUN NI'MAH (Jurnal Edukasi dan Penelitian Matematika, 2019)
Based on observations in class XI MIA SMA Negeri 2 Padang, it was found that students’ mathematical problem solving abilities were still low. One of the reasons is the learning applied is not optimal training and improving mathematical problem solving skill well. Efforts that can be used are implementing PBL models. The purpose of this study is to determine and discribe whether the ability of mathematical problem solving learning with the application of PBL models is better thanthe ability to solve mathematical problem learning by applying the direct learning model. This type of research is quasi experimental research design with Randomized Posttest-Only Control Group Design. The study population was students of class XI MIA SMA Negeri 2 Padang with a sample of class XI MIA2 and XI MIA3. The instrument used was a test of mathematical problem solving ability in the form of essay questions. The results showed the ability to solve mathematical problems with the application of PBL models is better thanthe ability to solve mathematical problems with the application of direct learning models.Keywords — Problem Based Learning (PBL), problem solving skill, Mathematics